Magmatic fractionation of trace elements in biotite with emphasis on indium in the Salmi batholith, Russian Karelia - Bäckström, Alice (2020)
Biotite is one of the most common ferromagnesian phases in granitic systems and has a crystal lattice allowing for a range of cation substitutions. The mineral can record whole rock chemistry, mirror processes in the rocks and indicate local metal enrichments. Biotite is thought to be a mineral preferentially incorporating indium which is a key metal for green technology such as solar panels. Indium enrichments have been found to be connected to rapakivi granites in southern Finland and western Russian Karelia. This thesis contains trace- and major element analyses of biotite collected from the Salmi rapakivi batholith in Russian Karelia which is connected to indium enrichments. The analyses are done by laser ablation inductive coupled plasma mass spectrometry (LA-ICP-MS) for evaluating the element behavior during magmatic fractionation in biotite. The use of biotite as an exploration vector for certain metals with emphasis on indium is also discussed as well as petrographic thin section descriptions of five granite types within the Salmi rapakivi batholithh. The petrography shows that the granite types from the inner part of the batholith exhibits textural similarities and can be discriminated from the granites in the more distant parts of the batholith. During magmatic fractionation the incorporation of Li into biotite is increasing as well as the amount of VIAl. The tin grades in biotite is also strongly affected by the fractionation process. Indium is found to be preferentially incorporated into biotite and/or amphibole if present, but indium is not seen to be affected by the fractionation process. In the biotite, no indium enrichment is identified thus the use of biotite as an exploration vector for the metal cannot be supported. But the clear enrichment of Sn displayed by biotite may be used in mineral exploration.